Use Of Differential Equations In Solving Filtering Problems, Solution By Euler, Heun And Runge-Kutt Methods - Asliddin Ne'matov (Genius Journals, 2025)
In this article, it is known from ordinary differential equation courses, if ' y f x, y = ( ) in a differential equation f x, y ( ) and if the equation is complex, to find the appropriate solution, it is important to use approximate methods. In this article, the concepts and examples of the approximate calculation of differential equations solved with respect to the derivative are considered.
Keywords: Differential equations; approximate solution; analytical solution